Efektivitas Program “Ngiung-Ngiung Hayuk” Dalam Menurunkan Kasus Kematian Ibu Di Puskesmas Lohbener Kabupaten Indramayu Tahun 2018 - Hasanah, Uswatun; Dartiwen, Dartiwen; Rudiansyah, Rudiansyah (Infokes, 2019)
The Maternal Mortality Rate (MMR) in West Java in 2015 was 823 cases while the Infant Mortality Rate (IMR) was 3,369 cases. The causes of maternal deaths were hypertension in pregnancy (31%), bleeding (30%), infection (4%), prolonged labor (1%) and others (34%). Of these figures, West Java is a contributor to maternal and newborn mortality rates with an average mortality of above 50%. This study aims to analyze how the efforts to implement the ngiung-ngiung hayuk  program in lowering the case of maternal mortality at the Lohbener Health Center in Indramayu Regency. The research method used in this study is mix methods, namely research that combines two forms of approaches in research (quantitative and qualitative). The subjects in this study were the Lohbener Health Center in Indramayu Regency, the person in charge of the Ngiung-ngiung Hayuk program and the high risk pregnant women in the Trimester III (> 28 weeks) as many as 27 people. The results of the study showed that the effort to implement this program was effective in lowering case of maternal mortality at the Lohbener Health Center in Indramayu district. It is hoped that this ngiung-ngiung hayuk program can be adopted by other health centers so that cases of maternal mortality can be suppressed.